Small dams and social capital in Yemen: how assistance strategies affect local investment and institutions - Vermillion, Douglas L.; Al-Shaybani, S. (International Water Management Institute, 2004)
This report examines the development of eight small dam projects in the mountainous province of Al-Mahweet in north-central Yemen. The report also investigates how external assistance affects incentives for local people to invest in dam development and water delivery systems and also to create rules, property rights and institutional arrangements to manage the dam and water.